STAGE III IRON DEFICIENCY ANEMIA IN ADULTS AND CHILDREN - Asrorov Akmal Aminjonovich (Web of Journals Publishing, 2025)
This article studied patients with IDA, determined the mild degree of the disease in children and highlighted the general condition of the examined patients. It is explained that it causes anemia, gastrointestinal tract problems, rickets, and frequent colds.
Keywords: IDA, starch, Asthenoneurotic syndrome, rickets, ARVI, lethargy, asthenia, apathy.